Experience of Domestic Violence Among Pregnant Women - Gurung, Saraj (Journal of Chitwan Medical College, 2013)
Pregnancy is seen as a time of joy and anticipation but sadly for some women it is a time when they suffer violence and abuse. Pregnancy can cause to stress in any type of relationship, and it’s a common cause of domestic violence. The emotional abuse and violence may begin or get worse during pregnancy. One third participants had experienced emotional and physical violence in present pregnancy. Participants experienced emotional violence such as: verbally abused, threatened to leave spousal house, threatened for remarriage, and restricted to enter the kitchen and their belongings were thrown out etc. Participants experienced punched, pushed on the floor/walls, slapped, kicked, beaten everywhere in the body, hit by fire wood and hair pulled. The causes were inter caste marriage, sub fertility, not working properly at home, dowry related and personal habits of alcoholism/ gambling of the husband etc. The consequences of domestic violence exhibited by the pregnant women felt pain and agony, feeling helpless, wanted to terminate pregnancy, wanted to break the marital relationship, feeling to suicide, backache, and high blood pressure. Experience of emotional violence is more prevalent than physical violence. Main causes of domestic violence are inter caste marriage, sub fertility, demanding of money and valuable things (dowry), drinking and gambling habit of husband and not working properly at home. Husbands and mother in-laws are the main perpetrators. Participants responded to domestic violence differently, by keeping silence, crying, and keeping busy in household chores and sharing/reporting to women groups. Journal of Chitwan Medical College 2013; 3(1): 51-55 DOI: http://dx.doi.org/10.3126/jcmc.v3i1.8467